2010
DOI: 10.1007/s10590-010-9085-2
|View full text |Cite
|
Sign up to set email alerts
|

Panning for EBMT gold, or “Remembering not to forget”

Abstract: A very useful service to the example-based machine translation (EBMT) community was provided by Harold Somers in his summary article which appeared in 1999, and was extended in our 2003 book Recent advances in example-based machine translation. As well as providing a comprehensive review of the paradigm, Somers gives a categorisation of the different instantiations of the basic model. In this paper, we provide a complementary view to that of Somers. Today's EBMT systems learn by analogy. Perhaps even more so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…that EBMT was also seen (as we have noted above) as a significant challenger to RBMT. Interestingly, Way (2009) notes that similar trends in the language used can be seen in EBMT papers at the time:…”
Section: Mathematical Formulation Of Smtmentioning
confidence: 76%
See 1 more Smart Citation
“…that EBMT was also seen (as we have noted above) as a significant challenger to RBMT. Interestingly, Way (2009) notes that similar trends in the language used can be seen in EBMT papers at the time:…”
Section: Mathematical Formulation Of Smtmentioning
confidence: 76%
“…To be fair, Lopez (2008) does cite one EBMT paper, but the steps taken to avoid the term 'EBMT' are remarkable. In Way (2009), we observed that There has undoubtedly been a colossal move away from RBMT to more statistical methods, but now the pendulum is swinging back (slowly) in the opposite direction . .…”
Section: Pb-smt and Other Models Of Translationmentioning
confidence: 88%
“…For good summaries of example-based MT (EBMT) (cf. Section 3.3), we encourage the reader to consult Somers (1999;2003b) and Way (2009b). The monograph by Carl and Way (2003) provides a representative sample of the myriad array of techniques used in EBMT.…”
Section: Further Readingmentioning
confidence: 99%